TECHNOLOGY OF PRODUCTION OF BIO CHEESES AND REQUIREMENTS FOR QUALITY OF USED MILK - I. B. BEGIMKULOV,; D. I. KHAZRATKULOVA,; R. R. KHAYDARALIYEV, (International Journal of Innovations in Engineering Research and Technology, 2021)
Along with the increase in livestock production, the quality and environmental friendliness of the finished product is one of the important indicators. The work discusses the technology of preparation of bio-cheese presented to bio-cheese and to the quality of milk used for the production of cheese.